Reactions to the Union Budgets by the Sectoral Indices of NSE - Rajamohan, S.; Muthukamu, M. (Indian Journal of Finance, 2015)
The Budget is a financial statement that shows the future economic activity of a country. Being the most watched event of the nation, it has an immediate impact on the behavior of the equity market. In India, NIFTY and SENSEX are the two important broader market indices that dance to the cues of the budget speech by the Finance Minister on the budget day. Depending on the nature of information, the other sectoral indices too behave either positively or negatively in the stock market. The present study examined the impact of the Union Budgets on the behavior of 11 sectoral indices of NSE based upon the indices' movement prior to and subsequent to the budget day. The event window period was categorized into short term, medium term, and long term, and for the analysis purposes, Wilcoxon matched pairs test was applied to measure the nature and extent of the impact of the budget.